Contribuições da matemática financeira para o ensino médio: o uso de tributos em tarefas de sala de aula - Pinheiro, Cláudio Júlio César (2016)
The aim of this research is to verify the contributions of the tribute studies of Financial Mathematics contents for High School. The income tax implicates several areas of public and private interests. The tax collection is one of the mainly public funds resources, it’s necessary for the accomplishment of state functions. To discuss the taxes history with Financial Mathematics relating to the student routine was the center of attention in this Master’s Thesis in the financial education construction of the participating subjects of the research. The task was developed, by lessons, in a private school in Votorantim, in São Paulo’s countryside. The research-professor worked with the subject of Mathematics all along the Middle School and High School; the peculiarity that appointed a qualitative nature research. To the produce of our labor’s information, initially we did a diagnostic with our students and we determined their acknowledge about the abbreviations and conventional taxes’ purposes in our society. We aim to present in this labor the meaning of each abbreviation (taxes’ initials), tax collection and distribution tax. We elaborated and applied lessons divided in two steps: the research about taxes and questions about applicability of taxes with financial mathematics contents. The leading question of our research had the following elaboration: What contributions the study of taxes can generate in the learning of financial mathematics for High School students? The outcomes of our research showed that to insert the student in the historical taxes context, associating them with questions related to social context of our research subjects, contributes to the learning of the financial mathematics program contents, which are usually approached by the perspective of formulas application and algorithms, meaningless.